GAMBARAN TINGKAT PENGETAHUAN MAHASISWA TINGKAT III KEPERAWATAN ANASTESIOLOGI TERHADAP PENGGUNAAN TERAPI ACUPRESSURE - Agra Darmawati, I Dewa Ayu; Anggaraeni, Komang Rosa Tri (Bagian Keperawatan Fakultas Kedokteran Universitas Sriwijaya, 2022)
Background: acupressure is the act of suppression on the activation point (trigger point), wherein in the case of pain the activation point is the same as the acupoint in acupuncture. Acupoint lies throughout the body that connects through a complex network of meridians. Each acupoint has a special effect on the body’s system, or it has a particular organ inside the body. The aim of the acupressure point is to promote circulation that is able the balance energy (Qi). There are several ways to apply the acupressure technic by pressuring, twisting, knocking, tapping, and pulling at specific points of the body. Knowledge of cognition is a very important domain in forming a certain person's actions through the components of knowledge, comprehension, application, analysis, synthesis dan evaluation. Aim: to find out the knowledge level of a third-year student in anesthesiology nursing in ITEKES Bali's use of acupressure as therapy. Methods: This study is a descriptive quantitative study using a cross-sectional approach to measure the knowledge level of a third-year student of anesthesiology nursing in ITEKES Bali’s use of acupressure as therapy. The study populations are all the students in the level of a third-year of anesthesiology nursing. The sampling method uses purposive sampling using questionnaires as the study instrument. Result: the data analysis showed a lacking in the level of knowledge. In the less category, the score was 25 to 55. The total respondents in the less category are 60 students from 117 willing to be respondents. The student’s total score that obtains the highest score was 88 meanwhile the lower score was 28 from 100 as the highest score in the questionnaires. Conclusion: The representation level of knowledge students in the nursing Anesthesiology in the third level have lacked knowledge about acupressure. Keywords: Knowledge, Acupressure, complementary and alternative therapy ABSTRAK Latar belakang: Acupressure adalah penekanan-penekanan pada titik pengaktifan (trigger point), di mana dalam hal nyeri titik pengaktifan adalah sama dengan titik akupuntur (acupoint). Acupoint terletak di seluruh tubuh yang terhubung satu sama lain melalui jaringan yang komplek dari meridian. Setiap acupoint mempunyai efek khusus pada sistem tubuh, atau dengan organ tertentu di dalam tubuh. Titik-titik acupressure (acupoint) bertujuan memperlancar sirkulasi sehingga tercapai keseimbangan energy (Qi). Ada beberapa cara untuk melakukan acupressure diantaranya dengan cara menekan, memutar, mengetuk, menepuk, dan menarik pada titik-titik tubuh tertentu. Pengetahuan atau kognitif merupakan domain yang sangat penting dalam membentuk tindakan seseorang (overtbehaviour) yaitu terdiri dari tahu, memahami, aplikasi, analisis, sintesis dan evaluasi. Tujuan: Penelitian ini adalah untuk mengetahui tingkat pengetahuan mahasiswa tingkat III keperawatan anastesiologi terhadap penggunaan terapi acupressure. Metode Penelitian: Penelitian ini merupakan penelitian kuantitatif deskriptif dengan menggunakan pendekatan cross-sectional untuk mengukur adalah untuk mengetahui tingkat pengetahuan mahasiswa tingkat III keperawatan anastesiologi terhadap penggunaan terapi acupressure. Populasi penelitian adalah seluruh mahasiswa regular tingkat III Keperawatan Anastesiologi ITEKES Bali. Pengambilan sampel secara purposive sampling dengan instrument penelitian berupa kuesioner. Hasil penelitian: dari hasil analisa data diperoleh tingkat pengetahuan mahasiswa sebagian besar kurang yaitu pada rentang skor 25 sampai dengan 55 dengan jumlah responden sebanyak 60 mahasiswa dari 117 responden. Pada total skor tingkat pengetahuan mahasiswa diperoleh skor tertinggi adalah 88 sedangkan skor terendah adalah 28 dari nilai 100 sebagai skor tertinggi pada kuesioner. Simpulan: Gambaran tingkat pengetahuan mahasiswa Keperawatan Anastesiologi tingkat III adalah pada level kurang pengetahuan tentang acupressure